(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Nursing research advocates for the highest quality of patient care by emphasizing evidence-based nursing practices. The attitude of students towards research serves as a driving force, inspiring them to actively participate in research endeavors, cultivate essential research skills, and implement research discoveries within clinical environments, ultimately enhancing positive patient outcomes. Aim: This study aims to examine undergraduate nursing students’ attitudes toward the research component to identify implications for enhancing teaching and learning practices. Materials and Methods: From March to August 2023, a descriptive cross-sectional study was conducted at the College of Nursing, AllamaIqbal Medical College, Jinnah Hospital Lahore, involving a convenient sample of n = 100 undergraduate students. Participants signed informed consent and completed a self-administered questionnaire consisting of 25 items rated on a Likert scale. Data analysis was conducted using SPSS version 23. Results: The majority of nursing students hold a positive attitude towards research, as evidenced by a mean score of 74.05% with a standard deviation of 6.580. A vast majority (91.2%) acknowledge the utility of research in their profession. Specifically, 86.88% of nursing students demonstrate a positive attitude towards research, while 72.75% recognize its significance in both professional and personal life. However, a notable proportion (41.2%) finds research challenging, viewing it as difficult, complicated, and stressful, with 55.3% expressing difficulty with statistical aspects. Conclusion: While a significant portion of students recognize the value of research in nursing and maintain a positive attitude towards it, some find the research course stressful. Many students express negative feelings and anxiety about the research process. To improve student experiences, it’s suggested to integrate research courses into pre-university curricula and involve statistical experts from research centers to teach effective learning strategies.